A Flora Dicroidium no Rio Grande do Sul: implicações bioestratigráficas - SOMMER, MARGOT GUERRA; KLEPZIG, MIRIAM CAZZULO; IANNUZZI, ROBERTO; ALVES, LAUREN SALLY (Pesquisas em Geociências, 1999)
A Triassic taphoflora identified in the Central Region of the State of Rio Grande do Sul, southern Brazil, represents an important biostratigraphic stage in the paleofloristic succession of the Paraná Basin. This megafloristic association is composed of compressed leaves, fronds and seeds of a “Dicroidium Flora” and shows a predominance of the Dicroidium genus, with several species, and other important taxa like Neocalamites sp, Cladophlebis sp, Tetraptilon aff, heteromerum, Ginkgoites Antarctica, Sphenobaiera sp, Podozamites sp, Nilssonia sp, Pteruchus sp and Carpolithus sp. Taking into account the stratigraphical distribution of different species of the Dicroidium genus, a biostratigraphic framework was established. The biostratigraphical position of this Triassic flora was established by comparison with Triassic floras from Argentina, South Africa and Australasia. Considering that the recognition of this Dicroidium Flora was based on limited outcrops belonging to one lithostratiphic level (Santa Maria Formation – Passo das Tropas Facies), it was impossible to establish a formal biostratigraphic zonation. Instead, at present time, an informal floristic interval, named “Dicroidium odontopteroides Flora” is proposed (Late Anisian to Late Ladinian, Middle Triassic).